2015
DOI: 10.1021/acs.analchem.5b02627
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Quantitation of Intact Recombinant Antibody Product Variants Using Mass Spectrometry

Abstract: Accurate and precise quantitative measurement of product-related variants of a therapeutic antibody is essential for product development and testing. Bispecific antibodies (bsAbs) are Abs composed of two different half antibody arms, each of which recognizes a distinct target, and recently they have attracted substantial therapeutic interest. Because of the increased complexity of its structure and its production process, as compared to a conventional monoclonal antibody, additional product-related variants, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…For comparison, KiH homodimers were prepared and assessed by SEC. Studies of KiH have reported covalent and noncovalent forms of KiH homodimers in which the noncovalent form lacks the disulfide bonds in the hinge but antibody halves are held together by interactions in the Fc (27,28). Noncovalent homodimers would be expected to migrate at the same V e as covalent homodimers by SEC but in nonreducing SDS-PAGE would disassemble into halves.…”
Section: Discussionmentioning
confidence: 99%
“…For comparison, KiH homodimers were prepared and assessed by SEC. Studies of KiH have reported covalent and noncovalent forms of KiH homodimers in which the noncovalent form lacks the disulfide bonds in the hinge but antibody halves are held together by interactions in the Fc (27,28). Noncovalent homodimers would be expected to migrate at the same V e as covalent homodimers by SEC but in nonreducing SDS-PAGE would disassemble into halves.…”
Section: Discussionmentioning
confidence: 99%
“…However, covalent and noncovalent knob homodimers in bsAb are undesired products, and it has been challenging to separate and quantify homodimers because these species and bsAbs often have similar physicochemical properties. An efficient strategy for unbiased quantitation of homodimers in bsAbs was introduced based on a standard addition approach using, knob hAbs (half antibodies) as a surrogate for the noncovalent knob homodimer, by chip‐based‐RPLC‐TOF‐MS analysis . The method demonstrated accurate and reproducible quantitation of homodimers resulting in precise quantitation of intact antibodies (Fig.…”
Section: Advancements In Glycan and Glycoprotein Profiling By Ms(/ms)mentioning
confidence: 99%
“…(A) Quantitation of intact recombinant antibody product variants using standard addition approach by MS. (B) Representative figures for MS data extraction, deconvolution, and normalization. Reprint with permission from .…”
Section: Advancements In Glycan and Glycoprotein Profiling By Ms(/ms)mentioning
confidence: 99%
“…Intact mass analysis has also been used for bispecific variants identification and quantitation. 9,11,12 Homodimers can potentially cause undesired bioactivity. In addition, because of their potentially unnatural structure and presumed low stability, the homodimers may be more prone to aggregate which may lead to increased immunogenicity.…”
mentioning
confidence: 99%